RELIGIUSITAS DALAM FILM AIR MATA DI UJUNG SAJADAH PADA APLIKASI YOUTUBE (KAJIAN ANALISIS ISI) - Zorifa An Najiah; Sainil Amral; Uli Wahyuni (Universitas Batanghari, 2025)
This research aims to describe the use of forms of religiosity in the film Air Mata di Ujung Sajadah. The research method employed to collect and analyze the data is a qualitative descriptive method. The data in this study consist of dialogue utterances containing the dimensions of belief, religious practices or rituals, religious feeling or experience, religious knowledge, and the dimension of effect or application found in the film Air Mata di Ujung Sajadah. The findings of this research indicate that there are utterances related to five forms of religiosity in the film. These five forms are: (1) the dimension of belief, (2) the dimension of religious practices or rituals, (3) the dimension of religious feeling or experience, (4) the dimension of religious knowledge, and (5) the dimension of effect or application. From these five forms of religiosity, a total of 136 utterances containing elements of religiosity were identified. The most dominant aspect found in the film is the religiosity dimension of feeling or experience, with 71 utterances, while the least dominant is the dimension of belief, with only 6 utterances.